Rol de enfermería en cirugía digestiva mínimamente invasiva: revisión sistemática de evidencia científica - Yupangui Cela, Gisela Estefanía (2025)
Minimally Invasive Digestive Surgery represents a transformative surgical methodology that has significantly transformed the panorama of surgical practises and presents substantial benefits. The objective of the study was to systematise the priority nursing interventions in the care of the perioperative patient undergoing minimally digestive surgery. As a methodology, an exhaustive search was carried out in several scientific databases, including PubMed, Scielo, Scopus, Dialnet and Google Scholar, following the guidelines established in the PRISMA Declaration. Following the implementation of the specific inclusion and exclusion criteria, a total of 18 studies were selected. The results indicate that, during the preoperative phase, patient education and psychological support are essential; however, there are variations in the degree of detail provided on family participation and the use of relaxation techniques. In the intraoperative phase, remarkable consistency is observed in compliance with aseptic protocols, monitoring of vital signs and the provision of technical assistance. In the postoperative phase, effective treatment of pain, vigilant surveillance of vital signs and the promotion of early mobilisation are considered essential interventions. In conclusion, nursing interventions are indispensable in all stages of Minimally Invasive Digestive Surgery. Empirical evidence underlines the need to standardise evidence-based interventions, adapted to the unique cultural and demographic attributes of each patient, to improve clinical outcomes and increase patient satisfaction.